Sustained Weight Loss and Improvements in Cardiometabolic Risk Factors in a Worksite-based Behavioral Program (FS18-04-19). (13th June 2019) - Das, Sai Krupa; Vail, Taylor; Silver, Rachel; Chin, Meghan; Blanchard, Caroline; Saltzman, Edward; Ceglia, Lisa; Roberts, Susan
Abstract: Objectives: To evaluate the effectiveness of a novel low-burden behavioral intervention (BI) for weight loss on changes in body weight and cardiometabolic risk factors when implemented with or without meal replacements (MR). Methods: Twelve worksites (≥300 employees each) in the Greater Boston area participated in a cluster-randomized controlled trial, with 8 worksites ( n  = 259 participants) allocated to the intervention group (IG) and 4 worksites ( n  = 76) to a wait-listed control group (CG). IG participants were further randomized to receive the BI, which emphasizes hunger and craving management via diet composition, for 18 months without or with MR (BI + MR). Weight and cardiometabolic variables were measured at baseline and 6 months for all groups, and also at 12 and 18 months in the IGs. Linear mixed models compared 6-month changes in % weight loss, body mass index (BMI), body fat, and cardiometabolic risk factors for all groups. Similar analyses were conducted for the BI and BI + MR groups at 12 and 18 months. Estimated means and standard deviations were calculated. Statistical models were adjusted for age, sex, baseline measurement, and worksite. Results: The study population was 83% female. The Mean ± SD for age and BMI were 47.9 ± 10.4 years and 32.9 ± 5.5 kg/m 2, respectively. At 6 months, average weight loss was 9.2 ± 7.2% for BI and 8.3 ± 7.0% for BI + MR. Weight loss was significantly greater in both IGs than the CG (both P  < 0.001), but not significant between IGs ( P  = 0.35). Similar results were observed for BMI and % body fat (both P  < 0.01). BI and BI + MR had significant reductions in glucose and triglycerides ( P  < 0.05) compared to the CG. Changes in total cholesterol and LDL were significantly greater in BI + MR compared to BI alone ( P  < 0.05). Clinically significant reductions in weight and cardiometabolic risk factors were sustained in the IGs at 12 and 18 months. Conclusions: To our knowledge, weight loss in this study was greater than previous scalable worksite-based interventions. Weight loss did not significantly differ between the BI and BI + MR groups, and MR use was associated with additional reductions in total and LDL cholesterol. These results demonstrate the feasibility of novel approaches to achieve clinically impactful weight management in worksite settings. Funding Sources: Nutrient Foods LLC.